2016
DOI: 10.3390/ijerph13090900
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Home-Based Environmental and Educational Intervention to Improve Health in Vulnerable Households: Southeastern Pennsylvania Lead and Healthy Homes Program

Abstract: This evaluation examined whether participation in a home-based environmental educational intervention would reduce exposure to health and safety hazards and asthma-related medical visits. The home intervention program focused on vulnerable, low-income households, where children had asthma, were at risk for lead poisoning, or faced multiple unsafe housing conditions. Home visitors conducted two home visits, two months apart, consisting of an environmental home assessment, Healthy Homes education, and distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Several articles in this Special Issue advance environmental health justice scholarship by documenting linkages between unequal environmental exposure and adverse health impacts associated with unsafe infrastructure and homes [5,14], substance use and addiction [15], and children’s obesity and academic performance [16]. Campbell et al [5] provide a detailed assessment of the recent drinking water crisis and lead poisoning in Flint, USA.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Several articles in this Special Issue advance environmental health justice scholarship by documenting linkages between unequal environmental exposure and adverse health impacts associated with unsafe infrastructure and homes [5,14], substance use and addiction [15], and children’s obesity and academic performance [16]. Campbell et al [5] provide a detailed assessment of the recent drinking water crisis and lead poisoning in Flint, USA.…”
mentioning
confidence: 99%
“…In addition to describing how this tragedy happened and why socially disadvantaged populations are at particularly high risk for lead exposure, Campbell et al discuss how childhood lead exposure and Flint-like events can be prevented from occurring in the future. Mankikar et al [14] examine whether participation in a two-month long environmental education intervention program reduces exposure to homebased environmental health hazards and asthma-related medical visits. Their home intervention program in southeastern Pennsylvania, USA, focused on low-income households where children had asthma, were at risk for lead poisoning, or faced multiple unsafe housing conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A subset of studies has demonstrated the value of community health workers and home-visiting professionals in environmental health interventions, and these studies explicitly incorporated self-efficacy into study design. Working with 150 urban families in a northeastern state, Mankikar, Campbell, and Greenberg [ 33 ] analyzed the influence of a home-based environmental health intervention on knowledge of environmental health hazards, presence of hazards in homes, and medical visits for children with asthma. Two home visits were conducted by community health workers and included a home assessment (with pre-/post-assessments), environmental education, and distribution of supplies.…”
Section: Resultsmentioning
confidence: 99%